A preparation method of wear-resistant high thermal conductivity carbon fiber ceramic material and brake pad

By preparing wear-resistant, high thermal conductivity carbon fiber ceramic materials, the problems of high friction coefficient and large wear caused by the large hardness gap in existing brake pad materials are solved, and the wear resistance and thermal conductivity of brake pads are improved, and the service life is extended .

CN118724606BActive Publication Date: 2025-02-14ZHEJIANG XINGHUI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411231210.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-02-14
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The existing brake pad materials have a large gap in hardness between the carbon phase and silicon carbide phase, resulting in high friction coefficient and large wear, which affects the reliability and stability of the brake system.

Method used

A method of preparing wear-resistant, high-thermal conductivity carbon fiber ceramic material, including preparing a three-dimensional needle-punching preform, cracking carbon by chemical vapor deposition, immersing in a mixture of furfurone resin and high entropy low boron compounds, and processing at high temperature , obtain wear-resistant and high heat conductivity carbon fiber ceramic materials.

Benefits of technology

The brake pads of this material have excellent wear resistance, improved thermal conductivity and extended service life, while bending strength and shear force are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724606B_ABST
    Figure CN118724606B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a wear-resistant and highly thermally conductive carbon fiber ceramic material and a brake pad, comprising the following steps: preparing a three-dimensional needle-punched preform; in an argon atmosphere, using methane or ethylene as a raw material, performing a cracking reaction, and cracking carbon on the three-dimensional needle-punched preform by chemical vapor deposition to obtain a carbon fiber with a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is impregnated with a mass ratio of (90-95): (5-10) of furfural resin and a high entropy low boron compound (NbCrMoWFe) B 0.8 The carbon / ceramic composite material is treated at 2700-2900°C for 46-50h to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material. The carbon fiber ceramic material is processed and polished to obtain a brake pad with excellent wear resistance and extended service life; it also has high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brake pads, and in particular relates to a preparation method of a wear-resistant and high-thermal-conductivity carbon fiber ceramic material and a brake pad. Background Art

[0002] Brake pads are key components in the braking system. They rub against the brake disc (or brake drum) to form a friction pair, generate braking torque, and convert the kinetic energy of the car into heat energy. The comprehensive performance of brake pads is directly related to the reliability and stability of the braking system.

[0003] At present, brake pads are mainly made of resin and filler mixed and then hot-pressed and sintered. They are semi-metallic or low-metallic resin-based composite materials; their main phase components are carbon phase and silicon carbide. The hardness difference between these two phases is large. When they are directly used as automobile brake pads for brake dual matching with carbon ceramic brake discs, there will be problems such as too high friction coefficient and excessive wear. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a method for preparing a wear-resistant and highly thermally conductive carbon fiber ceramic material and a brake pad. The ceramic material prepared by the method is used as a brake pad and has excellent wear resistance.

[0005] The present invention provides a method for preparing a wear-resistant and high thermal conductivity carbon fiber ceramic material, comprising the following steps:

[0006] Preparing a three-dimensional needle-punched preform;

[0007] In an argon atmosphere, methane or ethylene is used as a raw material for cracking reaction, and the three-dimensional needle-punched preform is cracked by chemical vapor deposition to obtain a density of 1.3-1.5 g / cm 3 Carbon-carbon composite materials;

[0008] The carbon-carbon composite material is impregnated with a furfural resin and a high entropy low boron compound (NbCrMoWFe)B in a mass ratio of (90-95):(5-10). 0.8 and then carbonizing to obtain a carbon / ceramic composite material;

[0009] The carbon / ceramic composite material is treated at 2700-2900° C. for 46-50 hours to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material.

[0010] Preferably, the carbonization temperature is 750-850° C., and the carbonization time is 11-13 hours.

[0011] Preferably, the furfural resin and the high entropy low boron compound (NbCrMoWFe)B 0.8 The mass ratio is 95:5 or 92:8 or 90:10.

[0012] Preferably, the density of the carbon / ceramic composite material is 1.6-1.9 g / cm 3 .

[0013] Preferably, the flow rate of methane or ethylene is 60-80 L / min;

[0014] The flow ratio of argon to methane is 1:3.8~4.2;

[0015] The flow ratio of argon to ethylene is 1:3.8~4.2.

[0016] Preferably, the pressure of the cracking reaction is 0.1-0.12 MPa; and the time of the cracking reaction is 5.5-6.5 h.

[0017] The present invention provides an automobile wear-resistant and high-thermal-conductivity carbon fiber ceramic brake pad, which is obtained by processing and polishing the material prepared by the preparation method described in the above technical scheme.

[0018] Preferably, the shear force of the brake pad is 6.1~8.3KN / cm 2 , hardness is 64~90HRS, wear rate is 0.14×10 -7 ~0.28×10 -7 cm 3 / Nm, thermal diffusion coefficient is 17.5~19.1 mm 2 / s.

[0019] The present invention provides a method for preparing a wear-resistant and highly thermally conductive carbon fiber ceramic material, comprising the following steps: preparing a three-dimensional needle-punched preform; using methane or ethylene as a raw material, performing a cracking reaction in an argon atmosphere, and cracking carbon on the three-dimensional needle-punched preform by chemical vapor deposition to obtain a carbon fiber with a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is impregnated with a mass ratio of (90-95): (5-10) of furfural resin and a high entropy low boron compound (NbCrMoWFe) B 0.8 The carbon / ceramic composite material is treated at 2700-2900°C for 46-50h to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material. The method uses methane or ethylene as a raw material for cracking reaction to obtain a carbon / ceramic composite material with a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is then impregnated with (90~95):(5~10) furfural resin and high entropy low boron compound (NbCrMoWFe)B 0.8The mixture is carbonized to obtain a carbon / ceramic composite material, and after high-temperature treatment, a wear-resistant and highly thermally conductive carbon fiber ceramic material is obtained. The brake pad obtained after the carbon fiber ceramic material is further processed and polished has high bending strength, excellent wear resistance, and extended service life; it also has high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A schematic diagram of the structure of a wear-resistant and highly thermally conductive carbon fiber ceramic brake pad for an automobile prepared according to an embodiment of the present invention;

[0021] Figure 2 This is a polarizing microscope image of pyrolytic carbon in the rough layer of the carbon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing a wear-resistant and high thermal conductivity carbon fiber ceramic material, comprising the following steps:

[0023] Preparing a three-dimensional needle-punched preform;

[0024] In an argon atmosphere, methane or ethylene is used as a raw material for cracking reaction, and the three-dimensional needle-punched preform is cracked by chemical vapor deposition to obtain a density of 1.3-1.5 g / cm 3 Carbon-carbon composite materials;

[0025] The carbon-carbon composite material is impregnated with a furfural resin and a high entropy low boron compound (NbCrMoWFe)B in a mass ratio of (90-95):(5-10). 0.8 and then carbonizing to obtain a carbon / ceramic composite material;

[0026] The carbon / ceramic composite material is treated at 2700-2900° C. for 46-50 hours to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material.

[0027] The method provided by the present invention uses methane or ethylene as a raw material for cracking reaction to obtain a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is then impregnated with (90~95):(5~10) furfural resin and high entropy low boron compound (NbCrMoWFe)B 0.8 The mixture is carbonized to obtain a carbon / ceramic composite material, and after high-temperature treatment, a wear-resistant and highly thermally conductive carbon fiber ceramic material is obtained. The brake pad obtained after the carbon fiber ceramic material is further processed and polished has high bending strength, excellent wear resistance, and extended service life.

[0028] The present invention first prepares a three-dimensional needle-punched preform. The present invention has no special restrictions on the method for preparing the three-dimensional needle-punched preform, and the three-dimensional needle-punched preform can be prepared by a process well known to those skilled in the art or purchased from a commercial product. The density of the three-dimensional needle-punched preform prepared by the present invention is 0.4-0.45 g / cm3 In a specific embodiment, the density of the three-dimensional needle-punched preform is 0.45 g / cm 3 .

[0029] In the present invention, methane or ethylene is used as a raw material for cracking reaction under an argon atmosphere, and carbon is cracked by chemical vapor deposition on the three-dimensional needle-punched preform to obtain a carbon having a density of 1.3-1.5 g / cm 3 In a specific embodiment, the density of the carbon-carbon composite material is 1.31 g / cm 3 , 1.32g / cm 3 , or 1.36 g / cm 3 . The flow rate of methane or ethylene is 60~80L / min; the flow ratio of argon to methane is 1:3.8~4.2. In a specific embodiment, the flow ratio of argon to methane is 1:4; the flow ratio of argon to ethylene is 1:3.8~4.2. The pressure of the cracking reaction in the present invention is 0.1~0.12MPa; the time of the cracking reaction is 5.5~6.5h. In a specific embodiment, the flow ratio of argon to methane or ethylene is 1:4; the pressure of the cracking reaction is 0.1MPa, and the time is 6h.

[0030] According to the present invention, rough pyrolytic carbon is generated after the preform is subjected to the chemical vapor deposition. The rough pyrolytic carbon has more stable properties, can improve the wear resistance of the brake pad, and prolong the service life.

[0031] The present invention impregnates the carbon-carbon composite material in a mass ratio of (90-95): (5-10) of furfural resin and high entropy low boron compound (NbCrMoWFe)B 0.8 The furfural resin and the high entropy low boron compound (NbCrMoWFe) B in the present invention are carbonized to obtain a carbon / ceramic composite material. 0.8 The mass ratio of is 95:5 or 92:8 or 90:10. The carbonization temperature is 750-850°C and the carbonization time is 11-13h. In a specific embodiment, the carbonization temperature is 800°C and the time is 12h.

[0032] The furfural resin in the present invention has a high carbon residue rate of about 60%, which can improve the densification efficiency of the preform, save the amount of resin used, and shorten the densification time; the high entropy low boron compound (NbCrMoWFe) B 0.8 After carbonization, a boron-containing compound can be generated to improve the thermal conductivity of the brake pad and make the brake pad dissipate heat faster; the present invention uses furfural resin and high entropy low boron compound (NbCrMoWFe) B 0.8 The mixture can reduce the high entropy low boron compound (NbCrMoWFe)B 0.8The invention adopts a specific mass ratio of furfural resin and a high entropy low boron compound as an impregnation liquid for a carbon-carbon composite material, so that the brake pad made of carbonized carbon fiber ceramic material has a higher bending strength.

[0033] The carbon / ceramic composite material is treated at 2700-2900°C for 46-50 hours to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material. After the composite material is treated at the above temperature, the carbon produced after the resin is carbonized is graphitized, which can improve the mechanical properties of the product and make the brake pad more wear-resistant. In a specific embodiment of the present invention, the carbon / ceramic composite material is treated at 2800°C for 48 hours.

[0034] The present invention also provides an automobile wear-resistant and high-thermal-conductivity carbon fiber ceramic brake pad, which is obtained by processing and polishing the material prepared by the preparation method described in the above technical solution.

[0035] Figure 1 This is a schematic diagram of the structure of an automotive wear-resistant and high thermal conductivity carbon fiber ceramic brake pad prepared in an embodiment of the present invention.

[0036] The invention adopts the above-mentioned material to prepare the brake pad in a short period of time, thereby improving production efficiency.

[0037] The present invention prepares carbon / ceramic brake pads of corresponding specifications and models after processing and grinding the materials.

[0038] The present invention performs quality inspection on the prepared carbon / ceramic brake pad, including testing of hardness, density, size and other indicators, and performs necessary trimming.

[0039] The present invention performs physical and chemical performance analysis on carbon / ceramic brake pad samples, wherein a shear test is performed according to standard GB / T22310-2008, a hardness test is performed according to GB / T5766-2007, a density test is performed according to JC / T685-2009, a wear rate test is performed according to GB / T11834-2000, a thermal diffusion coefficient test is performed according to GB / T22588-2008, and a bending strength test is performed according to ASTMC 1341-00.

[0040] In order to further illustrate the present invention, a preparation method of a wear-resistant and highly thermally conductive carbon fiber ceramic material and a brake pad provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0041] Example 1

[0042] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber tire net and a non-woven fabric, then layer a single layer of 0° non-woven fabric, tire net, 90° non-woven fabric, and tire net in a circular manner, and then use the needle with barbs on the edge to needle-punch the non-woven fabric and tire net. During the needle-punching process, the barbs bring the tire net layer fibers to the vertical direction, so that the non-woven fabric and the tire net are connected as a whole, and the density of needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0043] Preparation of the high entropy low boride ceramic (NbCrMoWFe) B 0 .8 The method comprises the following steps: preparing the required mixed powder: Fe powder, Nb powder, MoB powder, WB powder and CrB2 powder, the molar ratio of the raw material powder is Nb: Fe: MoB: WB: CrB2 = 1:1:1:1:1, using a balance to weigh 4.4g CrB2 powder, 6.4g MoB powder, 11.7g WB powder, 5.6g Nb powder and 3.4g Fe powder respectively; placing the weighed powder in an agate ball mill, adding 157.5g agate balls, the ball-to-powder ratio is 5:1, the mass ratio of large balls to small balls is 1:1, using vacuum silicone grease to seal the ball mill, and filling argon gas into the ball mill to prevent oxidation of the powder; mixing the powder on a planetary ball mill for 10 hours at a speed of 220r / min to prepare a mixed powder. Weigh 15g of the prepared mixed powder and put it into a graphite mold with good thermal conductivity, and use graphite paper to cover the inner wall of the graphite mold and the part in contact with the powder. The mold was placed in a hot pressing sintering furnace and the vacuum was 1.8×10 -2 Pa, the sintering temperature is set to 1400℃, and the temperature is kept at 600℃, 900℃ and 1200℃ for 10min respectively during the heating process, the heating rate is 10℃ / min, and the pre-pressure of 10MPa is used during the heating process; when the temperature rises to 1400℃, the control pressure is 30MPa, and the holding time is 2h. After the sintering process is completed, the sample is taken out when the furnace cools to room temperature, which is (NbCrMoWFe)B 0.8 .

[0044] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.32g / cm 3 Carbon-carbon composite materials; Figure 2 This is a polarizing microscope image of pyrolytic carbon in the rough layer of the carbon-carbon composite material prepared in Example 1.

[0045] Step 3: Add furfural resin (98wt%) and high entropy low boride (NbCrMoWFe) B to the carbon-carbon composite material in step 2. 0.8 The density of the obtained carbon steel was 1.82 g / cm 3 Carbon / ceramic composites.

[0046] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0047] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare carbon / ceramic brake pads of corresponding specifications and models.

[0048] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0049] The present invention tests the physical and chemical properties of carbon / ceramic brake pads according to the above test method, and the test results are: shear is 6.9KN / cm 2 , hardness is 74HRS, density is 1.81g / cm 3 The wear rate is 0.12×10 -7 cm 3 / Nm, thermal diffusion coefficient is 15.5mm 2 / s, and the bending strength is 169MPa.

[0050] Example 2

[0051] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber mat and a non-woven fabric, then layer a single layer of 0° non-woven fabric, a mat, a 90° non-woven fabric, and a mat in turn, and then use a needle with barbs on the edge to needle-punch the non-woven fabric and the mat. The barbs will bring the fibers of the mat layer to the vertical direction during the needle-punching process, so that the non-woven fabric and the mat are connected as a whole. The density of the needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0052] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.31g / cm 3 of carbon-carbon composite materials.

[0053] Step 3: Add furfural resin (95wt%) and high entropy low boride (NbCrMoWFe) B to the carbon-carbon composite material in step 2. 0.8 The density of the obtained product was 1.84 g / cm 3 Carbon / ceramic composites.

[0054] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0055] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare a carbon / ceramic brake pad of corresponding specifications and models.

[0056] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0057] The present invention tests the physical and chemical properties of carbon / ceramic brake pads according to the above test method, and the test results are: shear is 8.0KN / cm 2 , hardness is 85HRS, density is 1.83g / cm 3 , the wear rate is 0.10×10 -7 cm 3 / Nm, thermal diffusion coefficient is 17.4mm 2 / s, bending strength 181MPa.

[0058] Example 3

[0059] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber mat and a non-woven fabric, then layer a single layer of 0° non-woven fabric, a mat, a 90° non-woven fabric, and a mat in turn, and then use a needle with barbs on the edge to needle-punch the non-woven fabric and the mat. The barbs will bring the fibers of the mat layer to the vertical direction during the needle-punching process, so that the non-woven fabric and the mat are connected as a whole. The density of the needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0060] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.36g / cm 3of carbon-carbon composite materials.

[0061] Step 3: Add furfural resin (90wt%) and high entropy low boride (NbCrMoWFe) B to the carbon-carbon composite material in step 2. 0.8 The density of the obtained product was 1.90 g / cm 3 Carbon / ceramic composites.

[0062] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0063] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare a carbon / ceramic brake pad of corresponding specifications and models.

[0064] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0065] The present invention tests the physical and chemical properties of carbon / ceramic brake pads according to the above test method, and the test results are: shear is 8.6KN / cm 2 , hardness is 90HRS, density is 1.90g / cm 3 , the wear rate is 0.10×10 -7 cm 3 / Nm, thermal diffusion coefficient is 19.1mm 2 / s, and the bending strength is 188MPa.

[0066] Comparative Example 1

[0067] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber mat and a non-woven fabric, then layer a single layer of 0° non-woven fabric, a mat, a 90° non-woven fabric, and a mat in turn, and then use a needle with barbs on the edge to needle-punch the non-woven fabric and the mat. The barbs will bring the fibers of the mat layer to the vertical direction during the needle-punching process, so that the non-woven fabric and the mat are connected as a whole. The density of the needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0068] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.33g / cm3 of carbon-carbon composite materials.

[0069] Step 3: The carbon-carbon composite material in step 2 was added with furfural resin and impregnated at room temperature (8h) and carbonized (800℃, 12h) to obtain a density of 1.74g / cm 3 Carbon / ceramic composites.

[0070] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0071] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare a carbon / ceramic brake pad of corresponding specifications and models.

[0072] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0073] The present invention conducts physical and chemical performance analysis on the carbon / ceramic brake pad sample prepared in Comparative Example 1, and the results are as follows: shear strength is 6.8 KN / cm 2 , hardness is 74HRS, density is 1.78g / cm 3 The wear rate is 0.12×10 -7 cm 3 / Nm, thermal diffusion coefficient is 15.3mm 2 / s, and the bending strength is 165MPa.

[0074] Comparative Example 2

[0075] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber mat and a non-woven fabric, then layer a single layer of 0° non-woven fabric, a mat, a 90° non-woven fabric, and a mat in turn, and then use a needle with barbs on the edge to needle-punch the non-woven fabric and the mat. The barbs will bring the fibers of the mat layer to the vertical direction during the needle-punching process, so that the non-woven fabric and the mat are connected as a whole. The density of the needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0076] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.33g / cm 3 of carbon-carbon composite materials.

[0077] Step 3: Add phenolic resin (90wt%) and high entropy low boride (NbCrMoWFe) B to the carbon-carbon composite material in step 2. 0.8 The density of the obtained product was 1.79 g / cm 3 Carbon / ceramic composites.

[0078] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0079] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare a carbon / ceramic brake pad of corresponding specifications and models.

[0080] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0081] The present invention conducts physical and chemical performance analysis on the carbon / ceramic brake pad sample prepared in Comparative Example 2, and the results are as follows: shear strength is 6.5 KN / cm 2 , hardness is 71HRS, density is 1.73g / cm 3 The wear rate is 0.13×10 -7 cm 3 / Nm, thermal diffusion coefficient is 15.2mm 2 / s, and the bending strength is 156MPa.

[0082] Comparative Example 3

[0083] Step 1: Prepare a three-dimensional needle-punched preform. First, make the C fiber with the brand T700 into a short fiber mat and a non-woven fabric, then layer a single layer of 0° non-woven fabric, a mat, a 90° non-woven fabric, and a mat in turn, and then use a needle with barbs on the edge to needle-punch the non-woven fabric and the mat. The barbs will bring the fibers of the mat layer to the vertical direction during the needle-punching process, so that the non-woven fabric and the mat are connected as a whole, and the density of the needle-punched holes is 10 / cm 2 According to the required thickness, a three-dimensional needle-punched carbon fiber preform is obtained after repeated lamination and needle-punching. The density of the preform is about 0.45g / cm 3 The volume content of carbon fiber is about 40vol.%, and the layer density is about 14 layers / (10mm).

[0084] Step 2: Chemical vapor deposition (CVD) treatment. In an argon atmosphere, the methane or ethylene gas flow rate is 60L / min, the argon and methane gas flow ratio is 1:4, the system pressure is 0.1Mpa, 1100℃, heating for 6h, and the density is 1.33g / cm 3 of carbon-carbon composite materials.

[0085] Step 3: The carbon-carbon composite material prepared in step 2 was added to a mixture of furfural resin (90 wt%) and polymethylsilane (10 wt%) and impregnated at room temperature (8 h) and carbonized (800 °C, 12 h) to obtain a density of 1.75 g / cm 3 Carbon / ceramic composites.

[0086] Step 4: The carbon / ceramic composite material in step 3 is subjected to high temperature treatment at 2800° C. in a high temperature furnace for 48 hours.

[0087] Step 5: The carbon / ceramic composite material obtained in step 4 is processed and polished to prepare carbon / ceramic brake pads of corresponding specifications and models.

[0088] Step 6: Quality inspection and finishing: Conduct quality inspection on the prepared carbon / ceramic brake pads, including testing of hardness, density, size and other indicators, and perform necessary finishing operations.

[0089] The present invention conducts physical and chemical performance analysis on the carbon / ceramic brake pad sample prepared in Comparative Example 3, and the results are as follows: shear strength is 5.2 KN / cm 2 , hardness is 76HRS, density is 1.75g / cm 3 The wear rate is 0.13×10 -7 cm 3 / Nm, thermal diffusion coefficient is 15.9mm 2 / s, and the bending strength is 164MPa.

[0090] It can be seen from the above embodiments that the present invention provides a method for preparing a wear-resistant and highly thermally conductive carbon fiber ceramic material, comprising the following steps: preparing a three-dimensional needle-punched preform; in an argon atmosphere, using methane or ethylene as a raw material, performing a cracking reaction, and cracking carbon on the three-dimensional needle-punched preform by chemical vapor deposition to obtain a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is impregnated with a mass ratio of (90-95): (5-10) of furfural resin and a high entropy low boron compound (NbCrMoWFe) B 0.8 The carbon / ceramic composite material is treated at 2700-2900°C for 46-50h to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material. The method uses methane or ethylene as a raw material for cracking reaction to obtain a carbon / ceramic composite material with a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material is then impregnated with (90~95):(5~10) furfural resin and high entropy low boron compound (NbCrMoWFe)B 0.8The mixture is carbonized to obtain a carbon / ceramic composite material, and after high-temperature treatment, a wear-resistant and highly thermally conductive carbon fiber ceramic material is obtained. The brake pad obtained after the carbon fiber ceramic material is further processed and polished has excellent wear resistance and extended service life; it also has high thermal conductivity. The present invention tests the physical and chemical properties of the carbon / ceramic brake pad provided according to the above test method, and the test results are: shear is 6.9~8.6KN / cm 2 , hardness is 74~90HRS, density is 1.81~1.90g / cm 3 The wear rate is 0.10×10 -7 ~0.12×10 -7 cm 3 / Nm, thermal diffusion coefficient is 15.5~19.1mm 2 / s, and the bending strength is 169~188MPa.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A wear-resistant and highly thermally conductive carbon fiber ceramic brake pad for automobiles, which is made by processing and polishing a wear-resistant and highly thermally conductive carbon fiber ceramic material; The method for preparing the wear-resistant and highly thermally conductive carbon fiber ceramic material comprises the following steps: Preparing a three-dimensional needle-punched preform; In an argon atmosphere, methane or ethylene is used as a raw material for cracking reaction, and the three-dimensional needle-punched preform is cracked by chemical vapor deposition to obtain a density of 1.3-1.5 g / cm 3 The carbon-carbon composite material; the pressure of the cracking reaction is 0.1~0.12MPa; the time of the cracking reaction is 5.5~6.5h; The carbon-carbon composite material is impregnated with a furfural resin and a high entropy low boron compound (NbCrMoWFe)B in a mass ratio of (90-95):(5-10). 0.8 The mixture is then carbonized to obtain a carbon / ceramic composite material; the carbonization temperature is 750-850°C, and the carbonization time is 11-13 hours; the density of the carbon / ceramic composite material is 1.6-1.9 g / cm 3 ; The carbon / ceramic composite material is treated at 2700-2900° C. for 46-50 hours to obtain a wear-resistant and highly thermally conductive carbon fiber ceramic material.

2. The wear-resistant and highly thermally conductive carbon fiber ceramic brake pad for automobiles according to claim 1, characterized in that: The furfural resin and the high entropy low boron compound (NbCrMoWFe) B 0.8 The mass ratio is 95:5 or 92:8 or 90:

10.

3. The wear-resistant and highly thermally conductive carbon fiber ceramic brake pad for automobiles according to claim 1, characterized in that: The flow rate of methane or ethylene is 60~80L / min; The flow ratio of argon to methane is 1:3.8~4.2; The flow ratio of argon to ethylene is 1:3.8~4.

2.

4. The wear-resistant and highly thermally conductive carbon fiber ceramic brake pad for automobiles according to claim 1, characterized in that: The shear force of the brake pad is 6.1~8.3KN / cm 2 , hardness is 64~90HRS, wear rate is 0.14×10 -7 ~0.28×10 -7 cm 3 / Nm, thermal diffusion coefficient is 17.5~19.1 mm 2 / s.

Citation Information

Patent Citations

  • High-entropy low-boride ceramic and preparation method thereof

    CN113480315A

  • Densification method of carbon fiber preform

    CN114702330A

  • Cf / C-(TaNb, Ti, Zr, Hf) C composite material and preparation method thereof

    CN117003575A